2013
DOI: 10.1002/jssc.201200347
|View full text |Cite
|
Sign up to set email alerts
|

Fast microwave‐assisted extraction of rotenone for its quantification in seeds of yam bean (Pachyrhizus sp.)

Abstract: The aim of this study was to find if fast microwave-assisted extraction could be an alternative to the conventional Soxhlet extraction for the quantification of rotenone in yam bean seeds by SPE and HPLC-UV. For this purpose, an experimental design was used to determine the optimal conditions of the microwave extraction. Then the values of the quantification on three accessions from two different species of yam bean seeds were compared using the two different kinds of extraction. A microwave extraction of 11 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 17 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…Extraction of Rotenone and Cleanup Procedure. The microwave-assisted extraction (MAE) conditions were optimized in Lautie et al 24 MAE were performed in a closed-vessel system (MARS, CEM Corp., USA), and 20.0 mL of a 50:50 mixture of DCM/MeOH was placed in the glass extraction vessels with two stirring bars. The different vessels were placed into the extractor, which was programmed to make a cycle of 11 min at 55 °C, with the potency of the extractor set to 400 W. At the end of each extraction, the vessels were allowed to cool to 38 °C before opening.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Extraction of Rotenone and Cleanup Procedure. The microwave-assisted extraction (MAE) conditions were optimized in Lautie et al 24 MAE were performed in a closed-vessel system (MARS, CEM Corp., USA), and 20.0 mL of a 50:50 mixture of DCM/MeOH was placed in the glass extraction vessels with two stirring bars. The different vessels were placed into the extractor, which was programmed to make a cycle of 11 min at 55 °C, with the potency of the extractor set to 400 W. At the end of each extraction, the vessels were allowed to cool to 38 °C before opening.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…seed oil has been done by using MAE. It revealed that MAE of 11 min was more efficient as compared to 8 h of conventional Soxhlet extraction . Due to dipole spin and ionic conductance (specific properties of microwaves on the matter), microwave heating is rapid and occurs in the sample, which provided results in quick extractions.…”
Section: Maementioning
confidence: 99%